(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study sought to investigate the use of Social Networking Sites for academic communications by the LIS students of IGNOU-LSC, Pantnagar. A total of 94 questionnaires were administrated to all the students of BLIS and MLIS courses. 80 valid questionnaires were collected during the period of study. The study shows very highly interest among the respondent about use of social media sites. Facebook and WhatsApp with 100.0% usage and YouTube with 95.0% usage were found the top most used Social Networking Sites whereas WeChat with 15.0% was the least used Social Networking Site. Majority of the LIS students were using Social Networking Sites on their smartphones and about 40.0% respondents were using 1-2 hours per day.